Penerimaan Program Tablet Tambah Darah pada Remaja Putri di Indonesia: Penerimaan Program Tablet Tambah Darah pada Remaja Putri di Indonesia: Studi Literatur - Helmyati, Siti; Syarifa, Cut Alima; Rizana, Nisa Ayu; Sitorus, Nova Lidia; Pratiwi, Dessy (Amerta Nutrition, 2023)
Background: Anemia poses a significant challenge to the health and productivity of adolescent girls. This has prompted the Indonesian government to initiate a program to distribute iron and folic acid (IFA) supplements. Therefore, it is necessary to address the level of acceptance of or compliance with IFA supplementation among adolescent girls.   Objectives: This study aims to assess the acceptance level of the program among adolescent girls in Indonesia. Methods: A PRISMA-guided literature search was conducted in the NCBI, PubMed, Scopus, ScienceDirect, and Garuda databases for experimental or observational research published in Scopus-indexed journals from Q1 to Q4 or in Sinta 1 to Sinta 3 from 2013 to 2023.  Discussion: Eight studies conducted in five provinces in Indonesia showed that the coverage of IFA supplement distribution programs was less than 50%, with acceptance levels between 0% and 25.2% according to the Indonesian standard. The majority of IFA supplement distribution programs were not implemented in accordance with the standard. In addition, the supplements were not consistently provided every week, nor were they taken immediately at school. Factors that influence the consumption of IFA supplements among adolescent girls included knowledge, motivation, self-efficacy, attitude, parental influence, peer pressure, school policies and commitments, and the IFA supplements provided. Positive factors encouraged consumption, while negative factors discouraged consumption. Conclusions: The acceptance level of the IFA supplement distribution program remains low. To improve this, it is essential to increase the knowledge of adolescent girls and their parents about anemia, including its definition, causes, side effects, and symptoms, as well as the benefits and risks of not taking IFA supplements. Other necessary measures include improving the distribution system and providing supporting facilities.